Fashion & textiles : the essential careers guide - Brown, Carol (London : Laurence King, 2010)
Chapter 1 Creative Opportunities## womenswear, menswear, tailor, corporate wear, childrenswear, sportswear, swimwear, lingerie, bridalwear, woven textile designer, knitwear designer, print textile designer, costume designer, wardrobe assistant, accessory designer, footwear designer, milliner, fashion forecaster, colorist, illustrator, ##Chapter 2 Technical Opportunities ##production manager, pattern cutter, pattern grader, lay lanner, sample machinist, fabric technologist, garment technologist, costume/textile conservationist and restorer,## Chapter 3 Business and Management Opportunities ##buyer, buyer's administration assistant, assistant buyer, merchandiser, merchandising allocator, visual merchandiser, retail manager, retail assistant, independent retailer, personal shopper, recruitment agent/consultant, ##Chapter 4 Media Opportunities ##fashion editor, journalist, feature writer, fashion marketing manager, public relations officer, events planner/trade show organizer, fashion show producer, fashion stylist, make-up artist, fashion photographer, model, model booker, model scout, ##Chapter 5 Alternative Career Options ##university lecturer, research assistant, fashion/textile technician, art and design/textile teacher, art therapist, community artist, artist in residence, archivist, picture researcher, gap year, ##Chapter 6 Career Action Planning ##Chapter 7 Job Hunting ##Chapter 8 Preparing a Portfolio ##Chapter 9 The Recruitment Process ##Chapter 10 Starting Your New Job ##Chapter 11 Starting in Business ##Chapter 12 Moving Onward and Upward
boek